Simulation of the Flywheel Energy Storage System for an Industrial Robotic System - Yilmaz, Musa; Celikel, Resat; Aydogmus, Omur (Institute of Electrical and Electronics Engineers Inc., 2024)
The processes performed by industrial robots should not be interrupted. Power outages are an important reason for the disruption of production processes. FESS systems are an important energy storage system that has become more current in recent years. The important advantages of this system are that it does not have a half-life and can achieve high power density in a small volume. In this study, the energy of the robot performing an industrial process was provided by FESS. In this system operating at high speeds, energy production is achieved by using the L inductance between the inverter and the motor in the generator mode. While the system was working as a generator, the inverter was switched as a boost converter thanks to this inductance. Thus, DC link voltage was obtained for the robot power system. ©2024 IEEE.
2024 IEEE Global Energy Conference, GEC 2024 -- 4 December 2024 through 6 December 2024 -- Batman -- 207123
Keywords: Flywheel Energy Storage System; Industrial robots; Interruption of processes; Power outages